Lightweight composite material battery box lower box body and forming method thereof
By using thermally expanded epoxy foam and flame retardant foam as cores in the box under the composite battery box, the web reinforcement structure is designed, and the thermal expansion molding process is integrated molding, the local structural stress concentration and process complexity problems in the connection and molding process of the composite battery box under the composite battery box in the prior art are solved, and higher strength, stiffness and cost-effectiveness are achieved.
Patent Information
- Application Number
- CN202311017219.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-25
AI Technical Summary
The existing composite battery box under the box has problems such as concentrated local stress and easy to damage during the connection and forming process of the existing composite battery box, and the traditional molding process is complex and costly.
The thermally expanded epoxy foam and flame retardant foam are used as cores to design the web reinforced structure, and the composite material prepreg is integrated molded, and the lightweight composite material battery box is prepared by using the thermal expansion molding process.
The integrated molding of the box under the composite battery box is realized, which improves the strength and stiffness of the structure, reduces process complexity and cost, and enhances shear resistance.
Smart Images

Figure CN119518199A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery boxes, and in particular to a lightweight composite material battery box lower box and a molding method thereof. Background Art
[0002] As one of the most important components of new energy vehicles, the battery box plays a major role in protecting the battery cells. New energy vehicles face major challenges in lightweight structure. Therefore, composite battery boxes have become an important direction for the development of lightweight vehicles. At present, the mainstream lightweight solution for composite battery boxes is the prepreg compression molding process, but the traditional prepreg compression molding process is difficult to form large and complex structural parts, especially complex R angles and reinforced structures are prone to defects in product products. In the production of the lower box of the composite battery box, the split structure requires multiple parts to be formed separately and then connected. For composite materials, the connection will cause local stress concentration in the structure, which is easy to be damaged under the action of external forces, and the connection of multiple parts also increases the process cost. Therefore, there is an urgent need for a process that can give full play to the advantages of integrated molding of composite materials, while meeting the design of composite battery boxes with complex reinforced structures.
[0003] The foam sandwich structure has the functions of shock absorption and heat insulation, and can improve the stiffness of the structure by increasing the bending moment of the structure, so it is expected to reduce the design of complex reinforcement structures compared with metal battery boxes. However, the upper and lower panels of the traditional foam sandwich structure are separated, the strength of the foam core is low, and the interface between the foam core and the panel is prone to shear failure when subjected to external forces. Therefore, designing a web reinforcement structure inside the foam to connect the upper and lower skins into an integral structure will effectively improve the shear resistance of the structure, and in large assembly structural parts such as the lower box of the battery box, it involves the connection of built-in parts such as modules and water cooling plates. Therefore, the shear strength requirements of this sandwich structure are relatively high. At present, this type of web-reinforced sandwich composite material is mainly formed by a two-step method, and a complex mold is required to form the internal web structure, and then the foam core is embedded in the web structure and cured with the upper and lower skins. However, this molding method is relatively complicated, the process cost is also high, and the two-step method has limited improvement on the interface performance between the skin and the core. Therefore, using web-reinforced sandwich composite materials as the basic structure of the lower box of the battery box also requires new materials, new processes, and new structure designs to solve this series of existing problems. Summary of the invention
[0004] In order to solve the above-mentioned problems existing in the structure and performance of the lower box body of a battery box using a web reinforced foam sandwich composite material, the present invention uses a heat-expanding epoxy foam and a flame-retardant foam as a core, designs a web reinforcement structure in the core, and then lays the composite material prepreg together with the web structure and places the prefabricated product in a mold, locks the mold, heats and solidifies it to obtain an integrated web reinforced foam sandwich composite material battery box lower box body.
[0005] The technical solution of the present invention is:
[0006] A lightweight composite material battery box lower box body, wherein the reinforced structure, the lifting ears and the box body of the battery box lower box body are of an integrated design; the battery box as a whole is a foam sandwich composite material structure; a web reinforcement structure is designed inside the foam; the reinforced sandwich composite material battery box is formed in an integrated manner; a lightweight foam core is prepared into a designed shape; a heat-expandable foam prepreg is spread on the surface; and then a composite material prepreg is spread; the prefabricated product is compacted and put into a mold; the mold is locked and then heated and cured to obtain a lightweight composite material battery box lower box body.
[0007] Furthermore, a cross-reinforced structure is designed inside the foam, and multiple grooves are cut on the hard foam core. CFRP prepreg is laid in the grooves to achieve Z-direction reinforcement and interface reinforcement. At the same time, the upper and lower skins of the foam sandwich structure are connected as a whole to improve the strength and rigidity of the structure.
[0008] Furthermore, the foam core is a rigid foam with flame retardant properties, including any one of PMI, PET, PVC or PU.
[0009] Furthermore, the web reinforcement structure is a grid structure, and the upper and lower skins are connected as a whole through the web structure.
[0010] Furthermore, the lifting lug structure of the battery box for mounting on the vehicle body can also be formed in one piece, which reduces the assembly of the structure and integrates the preparation of the entire lower box of the battery box. The lifting lug can also be designed with a reinforced structure to improve the connection strength of the lifting lug.
[0011] Furthermore, the heat-expandable foam prepreg is prepared by adding a latent curing agent and a reinforcement to any one of an epoxy resin system, a polyurethane resin system, or a vinyl resin system, and then adding a foaming agent to form the heat-expandable foam prepreg.
[0012] Furthermore, the reinforcement is any one of glass fiber, amino-modified carbon fiber, basalt fiber or aramid fiber.
[0013] Furthermore, the preparation method of the amino-modified carbon fiber is as follows: adding the carbon fiber to sulfuric acid and nitric acid, heating and refluxing, filtering, washing with water, adding the oxidized carbon fiber to N,N-dimethylformamide, adding diethylenetriamine and N,N-dicyclohexylcarbodiimide, reacting at room temperature, filtering water, washing with ethanol, and obtaining the amino-modified carbon fiber.
[0014] Furthermore, the usage of diethylenetriamine and N,N-dicyclohexylcarbodiimide is 120-400% and 150-500% of the oxidized carbon fiber respectively.
[0015] Furthermore, during the curing process, the heat-expandable foam prepreg generates an expansion force of 0.1-10 MPa from the inside to the outside, and the curing and foaming reactions proceed simultaneously, generating a maximum expansion force before the resin gels, and the maximum expansion force is maintained between 30-60 minutes.
[0016] Furthermore, the molding process of the lower box of the lightweight composite material battery box is as follows:
[0017] (1) According to the design digital model of the battery box, reserve the size of the expanded foam and the size of the composite material, and then use CNC to carve out the lightweight foam core. The carved foam core also needs to consider the size space of the designed belly reinforcement structure. The belly reinforcement structure is designed on the side wall, bottom and ear position of the battery box. Grooves need to be carved at the position where the belly is designed. At the same time, each ear is designed with a belly structure. There is a groove structure in the foam core. When laying the prepreg, the groove position is the belly structure.
[0018] (2) Lay expandable foam prepreg at all locations in the foam structure where composite material prepreg is required.
[0019] (3) Based on the above-mentioned prefabricated product, the layer structure of the composite material prepreg is designed according to the material and structural strength, and then the cut prepreg is laid on the prefabricated product.
[0020] (4) After the prefabricated product is compacted, it is placed in a mold, and the mold is directly locked with bolts and placed in an oven for heating and curing, or the mold is placed on a press, locked with the pressure of the press, and then heated and cured. After cooling, demolding is performed to obtain an integrated composite lower box.
[0021] Furthermore, the heat-expandable epoxy foam adhesive controls the size of the foam expansion ratio and the size of the internal expansion force. A cavity exists between the mold and the prefabricated product, so that the prefabricated product can be placed in the mold. When the foam expands, the entire prefabricated product fills the mold to obtain a lightweight composite material battery box lower box.
[0022] Furthermore, the composite material prepreg and the mold are first heated to between 60-100°C, at which time the foaming agent in the expansion foam will not decompose, and the epoxy resin will react and prepolymerize. When the viscosity is controlled at 0.06-0.1Pa.s, the heat-expandable epoxy foam prepreg acts as an internal expansion source. When heated to 120-180°C, the foaming agent decomposes to produce gas molecules to form a foam body, and at the same time, an internal expansion force is generated to form a composite material. In this process, the foaming reaction and the curing reaction proceed simultaneously, and the generated internal expansion force can be maintained for more than 30 minutes, and a certain internal expansion force can be maintained at all times.
[0023] The beneficial technical effects of the present invention are:
[0024] The present invention uses a new type of sandwich composite material molding process to prepare the lower box body of the composite battery box, which can integrate the box body, lifting ears, reinforcement structure and other components of the lower box body. Compared with traditional compression molding and RTM processes, it speeds up the molding cycle of samples and saves costs.
[0025] Heat-expanding epoxy foam glue is mixed with another kind of rigid foam as the core. This kind of lightweight foam core has a better lightweight effect.
[0026] Diethylenetriamine was used to graft the carbon fiber surface, and the amino-modified carbon fiber was used as a reinforcement and added to the epoxy resin to form a heat-expandable epoxy foam prepreg. In the diethyltetramethylimidazole curing system, the amino groups grafted on the carbon fiber can be cured and cross-linked with the epoxy resin, thereby improving the interface compatibility between the carbon fiber and the epoxy resin and significantly enhancing the mechanical strength of the epoxy resin expansion foam.
[0027] A web reinforcement structure is designed in the foam core. This type of web reinforcement structure can significantly improve the strength and stiffness of the structure. It is prepared using a thermal expansion molding process, making the application of this type of web reinforced foam sandwich structure in the lower box of the battery box more feasible.
[0028] The heat expansion epoxy foam prepreg and the resin in the composite material belong to the same epoxy resin system. During the curing reaction, a chemical cross-linking reaction will occur at the interface between the foam and the composite material, which greatly improves the interfacial mechanical properties of the foam core and the composite material. When the battery box is subjected to complex external forces, it effectively prevents the debonding of the structural foam core and the skin structure.
[0029] The present invention designs the lower box of the battery box including the water-cooling plate, modules, other inserts and other connecting points, as well as the ear, the box body and other components into an integral structure, uses the thermal expansion foam prepreg as the internal expansion source, and uses the thermal expansion molding process for integrated molding. The entire lower box is a foam sandwich structure reinforced by the web. The web structure design inside the lightweight foam core can improve the strength and rigidity of the lower box structure of the battery box, thereby meeting the mechanical performance requirements such as battery box extrusion and bottom impact. The metal inserts pre-embedded with glass fiber prepreg in the internal lightweight core are combined with the composite material of the skin under the premise of preventing electrochemical corrosion, which can improve the connection performance of the structure, thereby meeting the performance requirements such as random vibration and mechanical impact of the battery box. The lower box of the battery box designed by the present invention combines the structure and the process together, giving full play to the advantages of integrated molding of composite materials. The prepared composite material battery box lower box has a faster production cycle, better lightweight effect, better performance, and higher industrialization potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the foam core of the lower body of the battery box after engraving: The hard load-bearing foam structure inside the lower body of the battery box can be made of PET, PVC, PMI foam, etc. This lightweight foam core can be engraved using block foam or directly formed by foaming in the mold. The groove design at the bottom and side of the foam core is to increase the web structure in the Z direction. Composite material prepregs such as CFRP and GFRP are laid at the web position to improve the Z-direction strength and stiffness and improve the interface bonding performance.
[0031] Figure 2 Schematic diagram of the groove design with a web structure in the foam structure: the composite prepreg is laid in the groove, and the prepreg of the skin structure can form an integral structure. This web structure can improve the Z-direction strength of the foam core and connect the composite material inside the lower box of the battery box as a whole, and then integrate it into a whole through a thermal expansion process.
[0032] Figure 3 Schematic diagram of typical belly plate structure prepreg laying: The belly plate structure of the lower box of the battery box is divided into two categories, one is the surface of the single hard foam core at the bottom, the expansion foam and composite material prepreg are laid on the surface, and the other is the expansion foam and composite material prepreg are laid in the grooves at the side walls and the ear positions.
[0033] Figure 4 Schematic diagram of the lower box sample of the battery box after molding
[0034] Figure 5 Mold diagram: The mold is made of 6061 aluminum alloy or steel and is made according to the outer envelope design of the integrated battery box lower box.
[0035] Figure 6 This is a schematic diagram of the R angle position. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0037] Example 1
[0038] Design and processing of foam core, such as Figure 1 The figure shows a PMI rigid foam core carved according to the designed digital model of the battery box. The side walls, bottom plate and lifting ears are all designed with web reinforcement structures. It can be seen that a groove with a width of about 30mm and a depth of about 0.8mm is designed on the side wall, and a groove with a width of 4mm penetrating the side wall is designed in the middle. A groove of the same size as the side wall is designed at the bottom to form a web reinforcement structure. In addition, a reinforced structure is designed on the bottom plate to meet the installation of the water cooling plate and the module, while improving the structural strength and rigidity. The lifting ear is the weak point of the integrated molded composite battery box. In order to meet the requirements of the extrusion test, multiple web structures connected from the side to the side are designed at the lifting ear, and the width of the groove is also 4mm.
[0039] Add carbon fiber to sulfuric acid and nitric acid, heat to 90°C and reflux for 3 hours, filter, wash with water, add oxidized carbon fiber to N,N-dimethylformamide, add 250% diethylenetriamine by mass of oxidized carbon fiber, and 150-500% N,N-dicyclohexylcarbodiimide, react at room temperature for 12 hours, filter water, wash with ethanol to obtain amino-modified carbon fiber.
[0040] Diethyltetramethylimidazole curing agent and 2% amino-modified carbon fiber reinforcement by weight of epoxy resin are added to epoxy resin, and then azobisisobutyronitrile as a foaming agent and EFKA2723 defoaming agent are added to form a heat-expandable epoxy foam prepreg.
[0041] When laying out the heat-expanding epoxy foam prepreg, try to remove the surface debris of the foam processed in the previous step, and then all positions need to be laid out with the heat-expanding epoxy foam prepreg. In addition, for the web reinforcement structure, the heat-expanding epoxy foam glue needs to cover the entire side wall, the bottom plate and the groove position that penetrates the side wall in the middle. The composite materials at the grooves of the side wall and the bottom plate involve more complex R-angle molding, so the expansion ratio of the heat-expanding epoxy foam glue is designed to be about 2 times, so that the internal expansion force generated is about 2MPa, which can better mold the web structure at the groove position. Similarly, for the ear position, the expansion foam needs to cover the surface and the groove. In fact, during the molding process, the design expansion ratio of the expansion foam at the groove position and other surfaces is slightly different. In order to achieve the lightweight effect, the other positions are designed to expand by about 3 times. The groove position has a complex R angle, so the design expansion is about 2 times. In this way, the lightweight effect can be improved as much as possible while meeting the molding process and structural performance.
[0042] Metal inserts are placed at the connection position. Considering the connection problem of pure composite materials, 3mm thick aluminum alloy and steel structure inserts are placed on the foam surface at the installation positions of water cooling plates, modules, relays, etc. In order to prevent electrochemical corrosion of metals, a layer of glass fiber prepreg is applied on the surface of the metal insert and then placed at the designed position.
[0043] Laying of composite prepreg. There is no need to lay adhesive film between the expansion foam and the composite prepreg, which is also the advantage of this molding process. The expansion foam and composite prepreg belong to the same epoxy resin system and can undergo chemical cross-linking reactions with each other to improve the mechanical properties of the interface. On the surface of the prefabricated product where the expansion foam has been laid in the previous step, the composite prepreg of the web structure is laid first, and the cut prepreg is passed through the designed groove position, thus connecting the inner and outer sides of the foam core. The width of the inner and outer wing panels is designed to be 20mm, so the connection dimension with the inner and outer skins has a width of 20mm, which is sufficient to ensure the designed connection strength. After laying the web structure, lay the composite prepreg on the surface layer by layer according to the design requirements.
[0044] The mold is preheated to 80°C, and the prefabricated battery box lower box is properly compacted and placed in the mold. According to production experience, it is generally placed in the female mold, and then the male mold is closed. The mold is as follows: Figure 3As shown. The mold can be directly fastened with bolts and then placed in an oven for 60 minutes. According to the curing characteristics of the resin and the decomposition temperature of the foaming agent, when it is close to the gel point and the viscosity is 0.06-0.1Pa.s, the oven temperature is set to 130°C. At this time, the resin will reach the gel point within 10 minutes, and the foaming agent in the thermal expansion epoxy foam prepreg will immediately decompose, reaching the maximum expansion force in about 3 minutes, and the maximum expansion force can be maintained for more than 30 minutes, so that the composite material can be well formed. The expansion foam will also fully fill all the gaps in the mold.
[0045] After the composite material is formed, the mold is cooled and then demoulded to obtain an integrated web-reinforced sandwich composite battery box lower box.
[0046] Comparative Example 1: The difference from Example 1 is that unmodified carbon fiber is used in the heat-expandable epoxy foam prepreg instead of amino-modified carbon fiber.
[0047] Comparative Example 2: The difference from Example 1 is that no amino-modified carbon fiber is added to the heat-expandable epoxy foam prepreg.
[0048] The mechanical properties of the lower box of the web reinforced sandwich composite battery box were tested using a universal material testing machine and a compression strength tester.
[0049] Tensile strength(MPa) Bending strength(MPa) Compression strength(MPa) Example 1 11.9 20.6 6.4 Comparative Example 1 10.1 15.1 5.3 Comparative Example 2 8.8 13.8 4.8
[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but such modifications are protected by patent law as long as they are within the scope of the claims of the present application.
[0051] In this process, considering the issue of industrialization, a press can be used for molding, and the mold can be fixed on the press. All processes such as preheating, product placement, heating, pressurization, and demoulding can be automated.
Claims
1. A lightweight composite material battery box lower box, characterized in that: The reinforced structure, lifting ears and box body of the lower box of the battery box are of integrated design. The battery box as a whole is a foam sandwich composite material structure. A web reinforcement structure is designed inside the foam. The reinforced sandwich composite material battery box is integrated into a mold. The lightweight foam core is prepared into a designed shape, and heat expansion foam prepreg is laid on the surface, and then the composite material prepreg is laid. The prefabricated product is compacted and put into a mold. After the mold is locked, it is heated and cured to obtain a lightweight composite material battery box lower box.
2. The lightweight composite material battery box lower box according to claim 1 is characterized in that: The invention designs a cross-reinforced structure inside the foam, cuts multiple grooves on the hard foam core, and lays CFRP prepreg in the grooves, which plays the role of Z-direction reinforcement and interface reinforcement. At the same time, the upper and lower skins of the foam sandwich structure are connected as a whole to improve the strength and rigidity of the structure.
3. The lower box of the lightweight composite material battery box according to claim 1 is characterized in that: The lifting ear structure of the battery box used for being mounted on the vehicle body is integrally formed, and the lifting ear can be designed with a reinforced structure.
4. The lightweight composite material battery box lower box according to claim 1, characterized in that: The heat-expandable foam prepreg is formed by adding a latent curing agent and a reinforcing body to any one of an epoxy resin system, a polyurethane resin system, or a vinyl resin system, and then adding a foaming agent.
5. The lower box of the lightweight composite material battery box according to claim 4 is characterized in that: The reinforcement is any one of amino-modified carbon fiber, glass fiber, basalt fiber or aramid fiber.
6. The lightweight composite material battery box lower box according to claim 4, characterized in that: The preparation method of the amino-modified carbon fiber is as follows: adding the carbon fiber to sulfuric acid and nitric acid, heating and refluxing, filtering, washing with water, adding the oxidized carbon fiber to N,N-dimethylformamide, adding diethylenetriamine and N,N-dicyclohexylcarbodiimide, reacting at room temperature, filtering water, washing with ethanol, and obtaining the amino-modified carbon fiber.
7. The lower box of the lightweight composite material battery box according to claim 6 is characterized in that: The usage of diethylenetriamine and N,N-dicyclohexylcarbodiimide is 120-400% and 150-500% of the oxidized carbon fiber respectively.
8. The lightweight composite material battery box lower box according to claim 1, characterized in that: The heat expansion foam prepreg generates an expansion force of 0.1-10 MPa from inside to outside during the curing process. The curing and foaming reactions are carried out simultaneously. The maximum expansion force is generated before the resin gels, and the maximum expansion force is maintained between 30-60 minutes.
9. A molding process for a lower box of a lightweight composite material battery box according to any one of claims 1 to 8, characterized in that: The molding process is: (1) Based on the design digital model of the battery box, the size of the expanded foam and the size of the composite material are reserved, and then the lightweight foam core is carved out using CNC. The carved foam core also needs to consider the size space of the designed belly plate reinforcement structure. (2) Lay expandable foam prepreg at all locations in the foam structure where composite material prepreg is required. (3) Based on the above-mentioned prefabricated product, the layer structure of the composite material prepreg is designed according to the material and structural strength, and then the cut prepreg is laid on the prefabricated product. (4) After the prefabricated product is compacted, it is placed in a mold, and the mold is directly locked with bolts and placed in an oven for heating and curing, or the mold is placed on a press, locked with the pressure of the press, and then heated and cured. After cooling, demolding is performed to obtain an integrated composite lower box.
10. The molding process of the lower box of the lightweight composite material battery box according to claim 9, characterized in that: The heat-expandable epoxy foam adhesive controls the size of the foam expansion ratio and the size of the internal expansion force. A cavity exists between the mold and the prefabricated product, so that the prefabricated product can be placed in the mold. When the foam expands, the entire prefabricated product fills the mold to obtain a lightweight composite material battery box lower box.
Citation Information
Cited By
Light aircraft front wing filling foam material and preparation method thereof
CN121182143A